Service Quality in Travel Tax Collection at Major International Airports: Towards Establishing A Customer- Centric Delivery Framework - Dolores T. Quiambao; Glaize Camille C. Nunag (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study aimed to assess the service quality of travel tax collection at two major international airports in the Philippines, Ninoy Aquino International Airport (NAIA) and Clark International Airport (CRK). Using the Service Quality (SERVQUAL) dimensions of reliability, responsiveness, assurance, empathy, and tangibility, the research examined traveler perceptions across different nationalities and traveler types. The primary objective was to identify service delivery gaps and develop a customer-centric framework to improve efficiency and satisfaction in travel tax services. A sequential explanatory mixed-methods design was employed, involving 400 travelers (N = 400) who completed structured surveys and 20 selected participants (N = 20) who participated in in-depth qualitative interviews. This mixed approach allowed for both statistical analysis and contextual understanding of the challenges faced in current service delivery practices. Findings indicated that although overall service quality was rated Good (Meets Expectations), key issues persisted, including prolonged waiting times, outdated systems, inconsistent communication, and limited support for priority passengers. Despite these concerns, no statistically significant differences were found in perceptions of service quality across traveler profiles, underscoring the need for uniform and inclusive service standards. To address these challenges, a Customer-Centric Delivery Framework was proposed. It consists of five core components: digitalization through a unified online platform, enhanced process efficiency, staff training and development, infrastructure upgrades, and a real-time feedback system. This framework aims to guide the development of more accessible, responsive, and traveler-focused tax collection services at NAIA, CRK, and other airport terminals nationwide.